STRATEGI PEMBELAJARAN AGAMA HINDU ABAD 21 - Putu Eka Sastrika Ayu (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
The primary role of teachers and schools is to equip students with new literacy, competence for the productive use of information technology, and a fairly disciplined conceptual knowledge base. This requires a change of student-centered learning. In such contexts, the teacher is a learning designer, the teacher's ability to plan learning in accordance with 21st century characteristics, one of them using a learning strategy. The material in the religious subjects is abstract, so it is necessary that the strategy can make students feel the benefits of learning in a konkrite.